IS THERE ANY EFFECT OF ADENOTONSILLECTOMY ON GROWTH? - Tunçcan, Tuncay; Kaygusuz, Irfan; Yalcın, Sınası; Karlıdag, Turgut; Keles, Erol; Akyiğit, Abdulvahap (My University, 2022)
Aim: To assess the effect of adenotonsillectomy for percentiles (on growth) on long times.\rMaterials and Methods: 36 boy and 24 girl underwent adenotonsilectomy when they were between 3.5 and 6 years in our clinic. Pre-operative families received weight and height measurements were taken, calculated percentiles. After 7 years we could achieved 49 patients and they were 31 boys and 18 girls, measured weight and height than calculated percentiles. The change in percentiles was compared.\rResults: Children with adenotonsillectomy have a percentile increase in weight in both boys and girls. Height percentile increased in boys but height percentile was the same in girls.\rDiscussion: Adenotonsillectomy resulted as an increase in weight percentile for long-term follow up but there was a significant increase in percentiles in boys and no change in girls.
Keywords: Genel ve Dahili Tıp; Kulak; Burun; Boğaz; Sağlık Bilimleri ve Hizmetleri; Pediatri